Umbilical cord plasma and salivary insulin and leptin concentrations in AGA neonates: a preliminary report. (November 2014) - Seal, Nuananong; Siddiqui, Danish S.; Seal, John; Bernhard, Kiley A.; Williams, Sumpan
Abstract Background and objective: Insulin and leptin hormones are important regulators of food intake and energy balance. There is limited information about insulin and leptin hormones in neonates. This preliminary study aimed to investigate the concentrations of insulin and leptin in umbilical cord plasma and neonate's saliva and their relationships. Methods: Umbilical cord plasma and salivary samples were obtained from 13 healthy, appropriate for gestational age (AGA) neonates. Insulin and leptin concentrations in umbilical cord plasma and saliva were measured using the MILLIPLEX MAP® Human Metabolic Hormone Magnetic Bead Panel. Results: Insulin concentrations in umbilical cord plasma correlates positively and significantly with leptin concentrations in umbilical cord plasma (r = 0.55, p = 0.04). Conclusions: More research is needed to explore the relationships between insulin and leptin hormones in neonate's saliva.